The current vision of the Chilean Judicial System - Marín Vallejo, Urbano (2007)
This article explains the organization of the Chilean Judicial Power system, which is going through a transition stage as a consequence of the deep reform that this institution has experienced. These changes have affected the judge's work and the users of the service of this institution, as well as a deep and very significant social and cultural impact.